2013
DOI: 10.1192/pb.bp.112.040097
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service discrimination against older people

Abstract: Aims and methodTo provide a picture of availability and equality of access to mental health services for older people prior to the Equality Act. In 2010, a questionnaire was sent to health commissioners in England, Scotland and Wales under a Freedom of Information request.ResultsOverall, 132 (76%) replied. Of 11 services, 7 were either unavailable or did not provide equality of access to older people in more than a third of commissioning areas. When provided by specialist older people's mental health, services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Older adults have historically had reduced access to psychological services; for example, Anderson et al (2012), in a survey of health commissioners in England, Scotland and Wales, found that psychotherapy was available to older adults in only 68% of services that they commissioned, compared with inpatient or community mental health care in 99% of services. In the first wave of the Improving Access to Psychological Therapy (IAPT) evaluation in England, older adults were under represented at 4% of those accessing therapy rather than at the expected rate of 12.5% allowing for the age profile of the population and the morbidity rate of this group (Department of Health, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults have historically had reduced access to psychological services; for example, Anderson et al (2012), in a survey of health commissioners in England, Scotland and Wales, found that psychotherapy was available to older adults in only 68% of services that they commissioned, compared with inpatient or community mental health care in 99% of services. In the first wave of the Improving Access to Psychological Therapy (IAPT) evaluation in England, older adults were under represented at 4% of those accessing therapy rather than at the expected rate of 12.5% allowing for the age profile of the population and the morbidity rate of this group (Department of Health, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of views about equity of specialist mental health support for older people without dementia 297 may explain our observations of the flow of new referrals to CMHTsOP, in which 1385 of these were not accepted for any assessment by the teams. Of these, we would argue that 61.5% were probably referred for dementia symptoms, as they were signposted on, prior to any evaluation, to memory clinics (see Appendix 3).…”
Section: Implications For Servicesmentioning
confidence: 88%
“…Services for older people have continued to lag behind those for younger people (Anderson 2013; Hilton 2015). Since the 1970s, policies for older people have appeared after those for younger people, reinforcing the idea that the needs of older people are less pressing.…”
Section: History Of Old Age Psychiatrymentioning
confidence: 99%
“…In the UK, a number of factors appear to have contributed to a move to integrate old age services with those of working-age adults, including changes in healthcare commissioning, the economic downturn since 2008, the cost pressures faced by the National Health Service (NHS), the austerity drive aiming for greater efficiency, and innovative use of available resources to meet the complex physical, psychological and social needs of the mentally ill (Anderson 2013; Warner 2014, 2015). With a growing older population there has also been an associated increase in the incidence of dementia.…”
mentioning
confidence: 99%